Hemodynamic follow‐up after valve‐in‐valve TAVR for failed aortic bioprosthesis. Issue 12 (23rd October 2022) - Wilbring, Manuel; Kappert, Utz; Haussig, Stephan; Winata, Johan; Matschke, Klaus; Mangner, Norman; Arzt, Sebastian; Alexiou, Konstantin
Abstract: Background: "valve‐in‐valve" TAVR (VIV‐TAVR) is established and provides good initial clinical and hemodynamic outcomes. Lacking long‐term durability data baffle the expand to lower risk patients. For those purposes, the present study adds a hemodynamic 3‐years follow‐up. Methods: A total of 77 patients underwent VIV‐TAVR for failing aortic bioprosthesis during a 7‐years period. Predominant mode of failure was stenosis in 87.0%. Patients had a mean age of 79.4 ± 5.8 years and a logistic EuroSCORE of 30.8 ± 15.7%. The Society of Thoracic Surgeons‐PROM averaged 5.79 ± 2.63%. Clinical results and hemodynamic outcomes are reported for 30‐days, 1‐, 2‐, and 3‐years. Completeness of follow‐up was 100% with 44 patients at risk after 3‐years. Follow‐up ranged up to 7.1 years. Results: Majority of the surgical valves were stented (94.8%) with a mean labeled size of 23.1 ± 2.3 mm and true‐ID of 20.4 ± 2.6 mm. A true‐ID ≤21 mm had 58.4% of the patients. Self‐expanding valves were implanted in 68.8% (mean labeled size 24.1 ± 1.8 mm) and balloon‐expanded in 31.2% (mean size 24.1 ± 1.8 mm). No patient died intraoperatively. Hospital mortality was 1.3% and three‐years survival 57.1%. All patients experienced an initial significant dPmean‐reduction to 16.8 ± 7.1 mmHg. After 3‐years mean dPmean raised to 26.0 ± 12.2 mmHg. This observation was independent from true‐ID or type of transcatheter aortic valve replacement (TAVR)‐prosthesis. Patients with a true‐ID ≤21 mm had a higher initial (18.3 ± 5.3 vs. 14.9 ± 7.1 mmHg; p = .005) and dPmean after 1‐year (29.2 ± 8.2 vs. 13.0 ± 6.7 mmHg; p = .004). There were no significant differences in survival. Conclusions: VIV‐TAVR is safe and effective in the early period. In surgical valves with a true‐ID ≤21 mm inferior hemodynamic and survival outcomes must be expected. Nonetheless, also patients with larger true‐IDs showed steadily increasing transvalvular gradients. This raises concern about durability.